The effect of multiple-network structure on divergent creativity of enterprise industrial cluster: The mediator of organizational resilience the moderator of organizational legitimacy - Yang, Fan; Chen, Sze-Ting (Edelweiss Applied Science and Technology, 2025)
In the context of advancing economic globalization and regional integration, industrial clusters not only confer competitive advantages and foster innovation but also enable firms to gain excess profits through knowledge spillovers. This study investigates the impact of multi-network structures on the divergent creativity of firms within these clusters. Drawing on survey data from 926 valid questionnaires, we employ structural equation modeling for our analysis. The results indicate that a multi-network structure positively influences the divergent creativity of firms. Furthermore, organizational resilience mediates this relationship, while organizational legitimacy acts as a positive moderator, strengthening the effect. This study explores the synergistic effect of multi-network structures and organizational resilience on divergent creativity within the industrial cluster context, thereby extending the theoretical boundaries of social network theory and industrial cluster theory. By innovatively introducing organizational legitimacy as a moderating variable, this research identifies its role as a key boundary condition in the interplay between multi-network structures, organizational resilience, and divergent creativity, thus offering new avenues for future research.